2015
DOI: 10.1242/dev.112904
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Costal 2-Fused interactions to Hedgehog signaling in Drosophila

Abstract: The Drosophila kinesin-family protein Costal 2 (Cos2) and its mammalian ortholog Kif7 play dual roles in Hedgehog (Hh) signaling. In the absence of Hh, Cos2 and Kif7 contribute to proteolytic processing and silencing of the Hh-regulated transcription factors, Drosophila Cubitus interruptus (Ci) and mammalian Gli proteins. Cos2 and Kif7 are also necessary for full activation of full-length Ci-155 and Gli transcription factors in response to Hh proteins. Here, we use classical fused alleles and transgenic Cos2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Our results provide a new output for FU as they show that it is likely to upregulate the levels of SMO directly at the cell surface and its signaling activity by phosphorylation. It is noteworthy that the FU-dependent phosphorylation of COS2 has been recently shown not to be essential for its activity as SMO and COS2 interact (Zadorozny et al, 2015); it is thus possible that the effect of FU on COS2 activity could in fact occur mainly via SMO. Our work also reveals that the FU downstream activity [i.e.…”
Section: Function and Regulation Of The Kinase Fumentioning
confidence: 99%
“…Our results provide a new output for FU as they show that it is likely to upregulate the levels of SMO directly at the cell surface and its signaling activity by phosphorylation. It is noteworthy that the FU-dependent phosphorylation of COS2 has been recently shown not to be essential for its activity as SMO and COS2 interact (Zadorozny et al, 2015); it is thus possible that the effect of FU on COS2 activity could in fact occur mainly via SMO. Our work also reveals that the FU downstream activity [i.e.…”
Section: Function and Regulation Of The Kinase Fumentioning
confidence: 99%
“…To date, the mechanisms by which Hh dissociates Ci-Cos2-kinases association and promotes Smo cell surface expression are still unclear. The previous studies have showed that Hh stimulates Cos2 differential phosphorylation on S572 and S931 [17], but the phosphorylation is not required for normal activation of Ci by Hh [18], suggesting that other mechanism is involved in this process.…”
Section: Introductionmentioning
confidence: 87%
“…Previously, such experiments showed that activated Fu alone was sufficient to elicit strong Hh target gene induction, suggesting that Ci-155 activation can be effective even without the normal inhibition of processing that occurs at the AP border (Zhou and Kalderon, 2011). Fu kinase activity is not required for Hh to block Ci-155 processing at the AP border (Alves et al, 1998;Ohlmeyer and Kalderon, 1998;Zadorozny et al, 2015). Nevertheless, synthetically activated Fu was observed to increase Ci-155 levels in anterior clones and further tests suggested this likely resulted from partial inhibition of Ci-155 processing mediated by Cos2 phosphorylation (Zhou and Kalderon, 2011).…”
Section: Dependence Of Ci-155 Activity Induced By Fused Kinase On Inhmentioning
confidence: 99%